Pengaruh Return on Investment (ROI) dan Economic Value Added (EVA) terhadap Kinerja Keuangan Perusahaan Manufaktur di BEI - Simbolon, David Hamonangan; Jefferson, Dedy Burju; Prasetiyo, Rudy (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the effect of ROI and EVA on the financial performance of manufacturing companies to provide insight and guidance for company management and investors in making more informed decisions. This study uses quantitative methods with a descriptive statistical approach to analyze the effect of ROI and EVA on the financial performance of manufacturing companies listed on the IDX in 2018-2023. The research sample amounted to 21 companies selected through purposive sampling technique, and the data was analyzed using multiple linear regression with classical assumption test to ensure proper regression model. This study found that ROI and EVA have a positive and significant effect on the financial performance of manufacturing companies, with ROI having a stronger impact. The regression model shows that 31.7% of the variability in financial performance can be explained by ROI and EVA, while the rest is influenced by other variables not discussed in this study. These results confirm the importance of managing ROI and EVA in financial strategy to improve the financial performance of companies.